ABSTRACT NOUNS IN DIGITAL DISCOURSE: A COGNITIVE-SEMANTIC AND PRAGMATIC ANALYSIS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article comprehensively studies the linguistic nature of abstract nouns at the intersection of semantics, cognitive linguistics, and discourse analysis. The study sheds light on the referential properties of abstract nouns, their conceptual nature, and their differences from concrete nouns on a scientific basis. The use of abstract nouns in the digital environment is explained by the expansion of their semantic and pragmatic functions. Based on a cognitive approach, abstract units are interpreted as linguistic expressions of concepts in human thinking. Also, the relationship between different levels of abstraction, semantic generalization, and conceptual categorization processes is analyzed. The results of the study show that abstract nouns do not represent real reality directly, but through a conceptual model formed in the human mind, and are an important tool for concisely conveying complex social, psychological, and cultural concepts in digital discourse.